2021
DOI: 10.1177/10901981211001863
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Influenza Vaccination During Pregnancy in Canada: Attitudes, Norms, Intentions, and Vaccine Uptake

Abstract: To improve uptake of influenza vaccine in pregnancy, it is important to understand the factors that predict prenatal vaccination. The aim of this study was to test the capability of the theory of planned behavior, augmented with information constructs, to predict and explain influenza vaccination uptake in a sample of 600 pregnant individuals in Canada. A baseline survey at the start of influenza season assessed beliefs, norms, perceived control, and information-seeking behavior related to influenza vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…In line with some previous studies conducted in other countries, such as the US, Canada, the Netherlands, Spain, Tunisia, and China [16][17][18][19][20]27], this study found a sizable gap between reported influenza immunization intentions and vaccine receipt in the next season. For instance, 64.7% of elderly patients with chronic diseases in Tunisia expressed a willingness to be vaccinated in the next season [27].…”
Section: Reported Influenza Vaccination Intentions and Vaccine Receip...supporting
confidence: 91%
See 4 more Smart Citations
“…In line with some previous studies conducted in other countries, such as the US, Canada, the Netherlands, Spain, Tunisia, and China [16][17][18][19][20]27], this study found a sizable gap between reported influenza immunization intentions and vaccine receipt in the next season. For instance, 64.7% of elderly patients with chronic diseases in Tunisia expressed a willingness to be vaccinated in the next season [27].…”
Section: Reported Influenza Vaccination Intentions and Vaccine Receip...supporting
confidence: 91%
“…A questionnaire (Supplementary Materials) was designed by the study team using a literature review [9][10][11][12][16][17][18][19][20][21] and was then administered to participants by the medical staff. Before fulfilling this questionnaire, patients were informed about the aim of the study and then assured that they would not be identified in any presentation or publication.…”
Section: Study Instrumentmentioning
confidence: 99%
See 3 more Smart Citations